America's inescapable crisis: Student homelessness. (April 2021) - Bishop, Joseph; Gonzalez, Lorena Camargo; Rivera, Edwin
Homelessness among U.S. K-12 students has been on the rise for decades, and it shows no signs of slowing down, especially as the COVID-19 pandemic has contributed to significant unemployment. Joseph Bishop describes findings from a study of student homelessness in California. Interviews with those experiencing homelessness and those who serve them, as well as analysis of the data, reveal the obstacles that prevent these communities from receiving the help they need. These include differing definitions of homelessness, limited funding being made available, and lack of training among the educators who could help identify and support students. Because of the multifaceted nature of the problem, groups at the local, state, and national levels must find ways to work together to arrive at solutions tailored to the need .